Alternativas de control para mancha marrón (Bipolaris oryzae) en el cultivo de arroz (Oryza sativa L.) en el Ecuador - Rodríguez Briones, Airton Alain (2025)
Rice (Oryza sativa L.) is a very important cereal worldwide. It generates employment for many families, adapts to diverse climatic conditions, and has a high nutritional value. Of the fungal diseases present in rice-growing areas, brown spot, caused by the fungus Bipolaris oryzae, represents a serious threat to the rice sector. This study aims to analyze control alternatives for brown spot in rice cultivation in Ecuador. This study consists of an exploratory research, with a non-experimental and bibliographic-documentary design, since no variables were manipulated. It was based on the collection, analysis, and interpretation of information from high-quality documents that allowed the synthesis, analysis, and summary of the collected information. The relevant topics on control alternatives for brown spot B. oryzae in rice cultivation (Oryza sativa L.) in Ecuador were specified. According to the analysis presented, it was determined that the life cycle of B. oryzae, the pathogen, begins its attack process in rice crops by dispersing its conidia. B. oryzae has a very complex life cycle that extends from sporulation to dispersal and penetration into rice tissues. For this reason, alternative control methods are necessary, such as Trichoderma spp. strains at 0.75 kg/ha, which act as biocontrol agents of the causative agent of this disease. The application of chemical fungicides, such as triazole at 500 cc/ha, azoxystrobin at 0.6 L/ha, and chlorothalonil at 0.8 L/ha (in single groups), has proven effective in critical rice crop situations.